2018
DOI: 10.1016/j.brainresbull.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of Fgf1 transcription by CRTC1 and memory enhancement

Abstract: Recent evidence demonstrates that epigenetic regulation of gene transcription is critically involved in learning and memory. Here, we discuss the role of histone acetylation and DNA methylation, which are two best understood epigenetic processes in memory processes. More specifically, we focus on learning-strength-dependent changes in chromatin on the fibroblast growth factor 1 (Fgf1) gene and on the molecular events that modulate regulation of Fgf1 transcription, required for memory enhancement, with the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 138 publications
(200 reference statements)
0
9
0
Order By: Relevance
“…; Uchida et al . ; Uchida and Shumyatsky ,b). The non‐canonical pathway for CREB activation might therefore direct the differential expression of target genes that were not studied before.…”
Section: Discussionmentioning
confidence: 99%
“…; Uchida et al . ; Uchida and Shumyatsky ,b). The non‐canonical pathway for CREB activation might therefore direct the differential expression of target genes that were not studied before.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium-signaling activation further sends its signal toward downstream epigenetic and transcription modulators, such as MEF2, MeCP2, and HDAC5. These pathways modulate gene expression that affects dendritic growth, synaptic development, and neuronal plasticity ( Greer and Greenberg, 2008 ; Graff and Tsai, 2013 ; Takemoto-Kimura et al, 2017 ; Uchida and Shumyatsky, 2018a , b ; Figure 1 ). Taken together, calcium-signaling stimulation through NMDARs and/or AMPARs activates multiple downstream nucleocytoplasmic pathways; it induces activity-dependent epigenetic genetic expression, contributing to depression and antidepressant action.…”
Section: The Glutamatergic System In Neuroplasticity Intracellular Signaling and Gene Expressionmentioning
confidence: 99%
“…All in all, acute intravenous administration of FGF-1 may become a new way for the treatment of PSCI in the future. Also, a genetic study revealed that FGF-1 may be involved in AD due to the obvious association of single nucleotide polymorphisms in FGF-1 gene, and the number of FGF-1-immunolabeled neurons decreases in AD patients, indicating that FGF-1 deficiency may be related to the pathophysiology of AD [21]. The increase of FGF-1 levels exerts a significant effect on glial cells and capillary proliferation, neurite outgrowth, and synapse formation.…”
Section: The Effects Of Fgfs On Psci Fgf-1 (Afgf)mentioning
confidence: 99%